2015
DOI: 10.1590/s0100-204x2015000400006
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield and reproductive performance of dairy heifers and cows supplemented with polyunsaturated fatty acids

Abstract: -The objective of this work was to determine productive and fertility responses of Holstein-Friesian heifers and cows to supplementation with extruded linseed and soybean as sources of polyunsaturated fatty acids (PUFAs). Supplementation had a positive effect on profitability, with significant increases in milk yield in supplemented cows, but not in heifers. Treatments had no effect on milk fat content, but higher milk protein contents were observed with supplementation. A higher conception rate was found for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The lack of effects of ELS on first-service conception rates in the present study may be attributable to the observed improvements in milk production in ELS-supplemented cows, which resulted in a negative energy balance. In addition, if, as in our study, a low number of cows were subjected to a first service, this may have contributed to the fact that there was no difference in the conception rate between the ELS-supplemented cows (44.4%) and those in the control (40.91%) [53].…”
Section: Discussionmentioning
confidence: 67%
“…The lack of effects of ELS on first-service conception rates in the present study may be attributable to the observed improvements in milk production in ELS-supplemented cows, which resulted in a negative energy balance. In addition, if, as in our study, a low number of cows were subjected to a first service, this may have contributed to the fact that there was no difference in the conception rate between the ELS-supplemented cows (44.4%) and those in the control (40.91%) [53].…”
Section: Discussionmentioning
confidence: 67%